Upstairs, downstairs. The complete series, v. 17-18 [videorecording (DVD)] - Baddeley, Angela, 1904-1976; Beeny, Christopher; Andrews, Anthony, 1948- (A & E Television Networks ; Distributed in the U.S. by New Video Group, 2005)
From the joyous days after the Armistice, when the laughter of children returns to the household, to the tragedy that befalls them, the saga of the Bellamy family and their servants reaches a bittersweet end.